Incorporation of Natural Blueberry, Red Grapes and Parsley Extract By-Products into the Production of Chitosan Edible Films - Dordevic, Simona; Dordevic, Dani; Sedlacek, Petr; Kalina, Michal; Tesikova, Karolina; Antonic, Bojan; Tremlova, Bohuslava; Treml, Jakub; Nejezchlebova, Marcela; Vapenka, Lukas; Rajchl, Ales; Bulakova, Monika (Polymers, 2021)
The aim of the research was to produce edible packaging based on chitosan with the addition of various concentrations of extracts of blueberry, red grape and parsley marcs. Packaging was made from extrudate extracts, which were subsequently analyzed by physicochemical methods: zeta-potential, gas barrier properties, thickness, water content, solubility, swelling degree, textural properties, total polyphenol content (TPC), polyphenols by high pressure liquid chromatography (HPLC), antioxidant activity, attenuated total reflectance Fourier-Transform spectroscopy (FTIR), antimicrobial activity and determination of migration of bioactive substances. The results indicate that a higher content of plant extracts have a statistically significant (p < 0.05) influence on properties of experimentally produced edible films. Edible films produced with the highest concentrations of red grapes marc extracts showed the most advantageous properties since antimicrobial activity against E. coli were the highest in this kind of produced film. The physical properties of edible films were also improved by the addition of extracts; gas permeability toward oxygen can be defined as advantageous, as can swelling degree, which decreased with higher concentrations of extracts. The research emphasized the possibility to use plant foodstuffs by-products in the production of edible/biodegradable films, helping in the overall sustainability and eco-friendliness of food/package production.
Keywords: FTIR; barrier properties; antioxidant activity; antimicrobial properties